Per-oral endoscopic myotomy (POEM): mid-term efficacy and safety - Martinek, Jan; Svecova, Hana; Vackova, Zuzana; Dolezel, Radek; Ngo, Ondrej; Krajciova, Jana; Kieslichova, Eva; Janousek, Radim; Pazdro, Alexander; Harustiak, Tomas; Zdrhova, Lucie; Loudova, Pavla; et al. (Surgical endoscopy, 2018)
BACKGROUND AND AIMS: Per-oral endoscopic myotomy (POEM) is becoming a standard treatment for achalasia. Long-term efficacy and the rate of post-POEM reflux should be further investigated. The main aim of this study was to analyze safety and mid-term (12 and 24 months) clinical outcomes of POEM. METHODS: Data on single tertiary center procedures were collected prospectively. The primary outcome was treatment success defined as an Eckardt score < 3 at 12 and 24 months. A total of 155 consecutive patients with achalasia underwent POEM; 133 patients were included into the analysis (22 patients will be analyzed separately as part of a multicenter randomized clinical trial). RESULTS: POEM was successfully completed in 132 (99.2%) patients, and the mean length of the procedure was 69.8 min (range 31-136). One patient underwent a drainage for pleural effusion; no other serious adverse events occurred. Treatment success at 3, 12, and 24 months was observed in 95.5% (CI 89.6-98.1), 93.4% (86.5-96.8), and 84.0% (71.4-91.4) of patients, respectively. A total of 11 patients (8.3%) reported initial treatment failure (n = 5) or later recurrence (n = 6). The majority of relapses occurred in patients with achalasia type I (16.7 vs. 1.1% achalasia type II vs. 0% achalasia type III; p<0.05). At 12 months, post-POEM reflux symptoms were present in 29.7% of patients. At 3 months, mild reflux esophagitis was diagnosed in 37.6% of patients, and pathological gastroesophageal reflux was detected in 41.5% of patients. A total of 37.8% of patients had been treated with a proton pump inhibitor. CONCLUSION: POEM resulted in greater than 90% treatment success at 12 months which tends to decrease to 84% after 2 years. More than one-third of the patients had mild reflux symptoms and/or mild esophagitis.
Keywords: výsledek terapie; Young Adult; Male; retrospektivní studie; mladý dospělý; Adolescent; následné studie; Adult; Aged; dospělí; mužské pohlaví; senioři; achalázie jícnu; Natural Orifice Endoscopic Surgery; endoskopické operace přirozenými otvory; mladiství; Follow-Up Studies; Treatment Outcome; lidé; Esophageal Achalasia; ženské pohlaví; Humans; Hellerova myotomie; Heller Myotomy; Retrospective Studies; Female; lidé středního věku; Middle Aged